BTHE TRANSFORMATION OF ISLAMIC EDUCATION AND ITS CONTRIBUTION IN THE AJATAPPARENG REGIONahasa Inggris: A Historical Perspective of Darud Da’wah wal-Irsyad - Mansur, Mansur; M. Ahdad, Muhakkamah; Jumiati, Jumiati; Fadillah, Nur (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: The transformation of Islamic educational institutions in Indonesia reflects broader efforts to adapt religious learning to modern sociocultural dynamics. In this context, Darud Da’wah wal-Irsyad (DDI) stands as a significant example of how pesantren-based organizations evolve to address both educational and social challenges in local communities. Purpose: This study examines the institutional transformation of Darud Da’wah wal-Irsyad (DDI) and its contribution to strengthening Islamic education and social values in the Ajatappareng region of South Sulawesi. Method: Using a qualitative approach through historical analysis and institutional document study, the research highlights how DDI has expanded its role from traditional Islamic schooling into a comprehensive system covering all levels of education, from early childhood to higher education. Result: The findings demonstrate that DDI integrates religious and general curricula, promotes character education, and nurtures Islamic scholars and intellectuals active at regional, national, and international levels. Conclusion These contributions illustrate the adaptive capacity of Islamic education in responding to sociocultural changes and community needs, while reinforcing its socio-religious role in a diverse society.